Stress and Anxiety among Pregnant Women attending Tertiary Care Hospital at Pokhara, Nepal (Nepal Medical College Journal, 2025)
Pregnancy is a period of great joy, also great stress to women both physically and mentally. Even in healthy women pregnancy may give rise to much anxiety because of anticipated uncertainty associated with it. The study aimed to assess the stress and anxiety among pregnant women. A descriptive cross-sectional research design was used. The study population consists of pregnant women who were 12-38wks pregnant and attending to Gynae/Obs OPD for regular checkup at Gandaki Medical College Teaching Hospital and Research Centre. Data were collected from Falgun 6 to Chaitra 25, 2080. A purposive sampling technique was used. Pregnancy Stress Rating Scale (PSRS) and Perinatal Anxiety Screening Scale (PASS) was used to collect the data. Collected data were entered, coded and edited into SPSS (16) and analyzed using both descriptive and inferential statistical methods. Of total 33.9% moderate, 32.6% had severe and 33.4% Eustress (normal stress) level of stress. There were no any statistically significant association between level of stress and selected variables. Similarly, 74.2% had minimal, 23.4% mild to moderate and 2.4% respondents have severe level of anxiety. Family support was statistically significant with level of anxiety during pregnancy (p=0.05). There was statistically significant of average positive correlation between stress and anxiety (r=0.605, p=0.001) among pregnant women. In majority of pregnant women have higher stress which reflect the higher anxiety.